EVALUATION OF SAFETY AND QUALITY MANAGEMENT IN CONSTRUCTION PROJECTS- A STUDY OF IBOM TROPICANA CONSTRUCTION PROJECTS - Amaka Chinweude Ogwueleka; Emaeyak I. Mendie (Journal of Construction Project Management and Innovation)
The nature of the construction industry necessities dangerous activities and the proper implementation of safety and quality management is essential to control hazards and wastes, and also to improve project success. This paper aims at adopting failure mode, effect and criticality analysis on an on-going project to investigate on how to improve safety and quality management in construction projects. In order to achieve this, the study evaluates the most critical factors influencing safety and quality management. Normative and empirical approaches are used for data collection. The possible failure mode of structural components and accident occurrence rate are analysed using the failure mode, effect and critically analysis sheets. Research findings reveal the possible causes and effects of failures and accidents. From the decision rule, the risk priority number is less than decision index number, which implies that risks/ hazards can be accepted and mitigated through the safety and quality policy designed to resolve the identified possible causes. The most critical safety and quality factors are identified as parameters for policy implementation.